The Gardens of Pannonhalma: Tourism Development of the Pannonhalma Benedictine Archabbey's Botanic Garden, Hospodár Garden and Lavender Garden - Szilágyi, Klára; Vajda, Szabolcs (4D Journal of Landscape Architecture and Garden Art, 2010)
The article presents the tourism development of the botanical garden, Hospodár Garden, and lavender field of the Pannonhalma Benedictine Archabbey. The study provides a detailed overview of the historical significance of the abbey’s gardens and the renovation efforts that began in the early 2000s, aimed at preserving the cultural and natural heritage of the area while promoting tourism. The article highlights landscape architectural solutions that balance historical traditions with modern needs. Special attention is given to the pathways, rest areas in the botanical garden, and the lavender field, which serve not only as aesthetic features but also as tourist attractions. As part of the development, an open-air theatre and meditation spaces were created in the Hospodár Garden, enhancing the recreational experience for visitors.
Keywords: Pannonhalma; Benedictine Archabbey; historic garden; tourism